Konsep Dasar Perancangan Wisata Gastronomi di Kecamatan Ubud, Gianyar - Sari, Anak Agung Istri Puspita; Kurniawan, Agus; Sastrawan, I Wayan Wirya (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Ubud District was proposed to be an international gastronomic tourism destination by the Ministry of Tourism and Creative Economy based on the United National World Tourism Organization (UNWTO) criteria and was established in 2018. The Ministry of Tourism and Creative Economy also encourages the development of creative economic tourism based on culture and local wisdom in Ubud District to revive economic activity so that can expand employment opportunities in the midst of a pandemic. Gastronomic tourism is a type of culinary tourism where tourists not only consume food but can also increase their knowledge about the food and the area from the original source. Gastronomic development in Ubud District is less than optimal and is still limited to a place for selling traditional culinary which only consists of one particular type of culinary at a food stall. By designing gastronomic tourism in Ubud District, Gianyar will become a place for culinary activities related to gastronomy and become a solution in overcoming these problems. The purpose of this study was to determine the basic concepts that will be used in the design of gastronomic tourism in Ubud District, Gianyar. The research method used is descriptive qualitative method. The results of this study produce a basic concept, namely cultural tourism based on culinary and local traditions.